Exploring EFL Teacher's Teaching Strategies During Emergency Remote Teaching - Sri Wulan Rahayu (Journal of Applied Linguistics (ALTICS), 2021)
This research investigated EFL teacher teaching strategies during emergency remote teaching. The COVID-19 pandemic prompted the government to proclaim the conversion of learning activities to online learning. The policy, as well as its relationship to teacher strategies in teaching English, is worth investigating. This study aimed at answering the following research questions: (1) What are the English teacher strategies for online teaching? (2) To  what  extent  do  the  strategies  help the English teachers in online teaching? This study used descriptive qualitative method and data were obtained through the use of questionnaire and interview. The data from interview were analyzed by coding, data reduction, data display, and drawing conclusion. The findings revealed that the strategies used by the teachers in teaching English are so various. For speaking skill, the teachers applied cooperative activity and drilling. For listening skill, the teachers used teaching bottom-up processing in which students must be able to recognize important key word. As for reading skill, the teachers applied several strategies such as inferring and question-answer relationship. Last, for writing skill, the teacher used conference. The strategies used by the teachers in teaching four skills of English are considered to be very helpful for the teachers. The strategies that they used really help the student learning process during this pandemic. Also with these strategies, they can find out the development of students' skills.